2014
DOI: 10.7314/apjcp.2014.15.21.9505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stellate Ganglion Block on the Peri-operative Vasomotor Cytokine Content and Intrapulmonary Shunt in Patients with Esophagus Cancer

Abstract: Asian Pac J Cancer Prev, 15 (21), 9505-9509 IntroductionOne-lung ventilation (OLV) has been widely applied to cardiothoracic surgery. In spite of unilateral lung ventilation during OLV, bilateral lungs are perfused, which is bound to result in reduced oxygenation, even hypoxemia (Karzai et al., 2009). Hypoxic pulmonary vasoconstriction (HPV) is a phenomenon that the body regulates respiratory and circulatory functions to maintain the oxygen supply within the normal range under the conditions of decreased oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Another randomized, double blind, placebocontrolled study (Kumar et al, 2014) showed that SGB had a significant analgesic effect on orthopedic upper limb surgery, additionally measured by opioid consumption. García-Morán et al (2013) and Guo et al (2014) demonstrated a favorable effect on perioperative stressrelated cytokine production. Sympathetic hyperactivity is regulated not only peripherally, but also centrally via the hypothalamus (Amino et al, 2007;Taneyama and Goto, 2009), and therefore SGB also improved chronic inflammatory bowel disease (ulcerative colitis), as shown as an additional intervention with sulfasalazine medication.…”
Section: Sgb In Other Situations Of Inflammation or Acute Hyperinflammation (Cytokine Storm)mentioning
confidence: 95%
“…Another randomized, double blind, placebocontrolled study (Kumar et al, 2014) showed that SGB had a significant analgesic effect on orthopedic upper limb surgery, additionally measured by opioid consumption. García-Morán et al (2013) and Guo et al (2014) demonstrated a favorable effect on perioperative stressrelated cytokine production. Sympathetic hyperactivity is regulated not only peripherally, but also centrally via the hypothalamus (Amino et al, 2007;Taneyama and Goto, 2009), and therefore SGB also improved chronic inflammatory bowel disease (ulcerative colitis), as shown as an additional intervention with sulfasalazine medication.…”
Section: Sgb In Other Situations Of Inflammation or Acute Hyperinflammation (Cytokine Storm)mentioning
confidence: 95%
“…Sympathetic overactivity means high neuron density of STG . STG block reduces pulmonary arterial resistance . STG block prevents lung injury .…”
Section: Discussionmentioning
confidence: 99%
“…22 STG block reduces pulmonary arterial resistance. 23 STG block prevents lung injury. 24 Bilateral STG block reduces pulmonary capillary wedge pressure.…”
Section: Sympathetic Networkmentioning
confidence: 97%
“…[20] Suppression of the inflammatory response decreases pulmonary vascular resistance and improves blood and air distribution in the lungs, thereby reducing pulmonary hypertension. [21] Second, by suppressing phospholipase A2 expression, the SGB can prevent lung edema and alveolar damage. [22] According to related research, the SGB protects the lungs from injury by reducing the release of surfactant protein A factors Yuan and Chen • Medicine (2024) 103:21 www.md-journal.com when 1 lung is on ventilation.…”
Section: Groupmentioning
confidence: 99%